2012
DOI: 10.1103/physreva.85.023829
|View full text |Cite
|
Sign up to set email alerts
|

Limits on the deterministic creation of pure single-photon states using parametric down-conversion

Abstract: Parametric down-conversion (PDC) is one of the most widely used methods to create pure single-photon states for quantum information applications. However, little attention has been paid to higher-order photon components in the PDC process, yet these ultimately limit the prospects of generating single photons of high quality. In this paper we investigate the impact of higher-order photon components and multiple frequency modes on the heralding rates and single-photon fidelities. This enables us to determine the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
122
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 63 publications
1
122
0
Order By: Relevance
“…Previous theoretical considerations of spatial multiplexing schemes utilising PDC have shown that by multiplexing several non-deterministic sources together, deterministic operation can be approached [86] . Christ and Silberhorn [86] examined the impact of multi-photon emission and multiple spectral modes on the performance of spatially multiplexed systems.…”
Section: Multiplexing: a Route To Deterministic Operationmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous theoretical considerations of spatial multiplexing schemes utilising PDC have shown that by multiplexing several non-deterministic sources together, deterministic operation can be approached [86] . Christ and Silberhorn [86] examined the impact of multi-photon emission and multiple spectral modes on the performance of spatially multiplexed systems.…”
Section: Multiplexing: a Route To Deterministic Operationmentioning
confidence: 99%
“…Christ and Silberhorn [86] examined the impact of multi-photon emission and multiple spectral modes on the performance of spatially multiplexed systems.…”
Section: Multiplexing: a Route To Deterministic Operationmentioning
confidence: 99%
See 2 more Smart Citations
“…An HPS is a photon-pair source in which one photon of each photon-pair is detected at the source to trigger a heralding signal that could be used to herald the presence of the other photon of the same pair [13][14][15][16][17][18][19]. As the detected photon plays a heralding role, it is called the heralding photon.…”
Section: Introductionmentioning
confidence: 99%